Hypertrophic cardiomyopathy in dog - Case report (Research, Society and Development, 2022)
Among the cardiac abnormalities, Hypertrophic Cardiomyopathy (HCM) has been described as the most common disease in companion animals, and is characterized by anatomical changes that lead to an increase in myocardial contractile fibers, thus providing total heart muscle enlargement and its dysfunction. Given its clinical importance and ability to lead the patient to sudden death, we aimed to report a case of hypertrophic cardiomyopathy in a dog, addressing its clinical and anatomopathological aspects. A 9-month old male dog of the breed Spitz German Dwarf was seen in a Veterinary Clinic in the city of Santarém - PA, with clinical complaint of sudden cardiac arrest after being released for recreation in a Pet Hotel. The physical evaluation showed dyspnea, cyanosis, limb rigidity, tachycardia (210 bpm) and temperature of 37.8ºC. After initial care, the patient had cardiorespiratory arrest, and even with resuscitation protocol, the patient died. A necropsy was performed, where cardiac alterations typical of HCM and acute myocardial infarction were found. It was observed that HCM causes numerous anatomical changes in the heart, where the increased thickness of the ventricular muscles and septum are the most striking changes during necroscopic examination and cause or not, clinical signs to the carrier of this disease. Almost always HCM leads to cardiac dysfunctions that range from decreased cardiac output to thrombus formation and myocardial infarction due to vascular complications of the coronary vessel network, causing sudden death of the animal, as can be seen in the present report.